Bacterioplankton community structure and molecular ecological network characteristics in the overlying water of Sancha Lake - Yong Li; Sidan Gong; Huan Liu; Yajie Li; Wenjia Luo; Zhilian Gong (PLoS ONE, 2025)
With the rapid development of society and economy, most lakes in southwest China are in a state of eutrophication. As decomposers and producers in lake ecosystems, the overlying water bacterioplankton communities play an important role in maintaining material circulation and energy flow. However, the response mechanism of their composition to eutrophication remains unclear. This research sampled the overlying water of Sancha Lake, a typical sub-deep-water lake in Southwest China, at nine different sampling sites in April (spring) and November (autumn) 2017. High-throughput sequencing of 16S rRNA gene and molecular ecological network approach are used to analyze the structure and network topology of bacterioplankton community and the response mechanism of key species to eutrophication in the overlying water of Sancha Lake. The results show that the bacterial species diversity is abundant, belonging to 55 phyla, 64 classes and 732 genera. Pseudomonadota, Actinomycetota and Bacillota are the dominant phyla, while Pseudomonas and Bacillus are the dominant genera. The relative abundance of bacterial groups in the overlying water in spring and autumn has significant seasonal differences (P < 0.05 or P < 0.01). There are seasonal differences between spring and autumn in bacterioplankton community structure in the overlying water (P < 0.01). The bacterioplankton community structure is mainly influenced by phosphorus, permanganate index (CODMn), dissolved oxygen (DO) and pH. In spring and autumn, the overlying water bacterioplankton communities are mainly affected by deterministic processes and random processes, respectively. In spring and autumn, there are more positive interactions than negative interactions among bacterioplankton in the overlying water. The closeness of the overlying water bacterioplankton network is higher in spring than in autumn, and the interaction degree of the components of the overlying water bacterioplankton network is higher in autumn than in spring. The key species in the spring bacterioplankton molecular ecological network are Methylobacter, Candidatus Magnetoovum, Pseudomonas and Thiobacillus. In autumn, Methylacidimicrobium, Thiothrix and Clostridium are found. The relative abundance of key species is positively correlated with soluble reactive phosphate (SRP) content in spring, but negatively correlated with SRP content in autumn. The results of this research indicate that the bacterioplankton community in the overlying water of Sancha Lake is abundant in diversity, and its composition and structure changes are dynamic responses to the changes of eutrophication environmental factors, and the key species of bacterioplankton may play an important role in the phosphorus cycle of eutrophication.